Effects of porcine reproductive and respiratory syndrome virus on porcine alveolar macrophage surface protein expression - Pullen, Rebecca Royale (Kansas State University, 2009)
Currently, porcine reproductive and respiratory syndrome virus (PRRSV) is the most economically significant disease affecting the swine industry. PRRSV is known for its restricted cell tropism, primarily infecting porcine alveolar macrophages (PAM) via receptor-mediated endocytosis. PRRSV infects only a portion of the PAM population both in vivo and in vitro, which suggests that not every macrophage is PRRSV-permissive. Three surface proteins that can act as receptors for PRRSV have been identified on PAM, however, little else is known about the regulation of macrophage tropism. Factors determining cellular permissibility or resistance to PRRSV infection remain largely uncharacterized, although a recent study from our laboratory demonstrated that 1) permissiveness to PRRSV infection increased with time in culture, 2) macrophages from infected pigs could be superinfected, and 3) addition of actinomycin D, which inhibits mRNA synthesis, blocked infection. These data suggest that a PRRSV-permissive subpopulation of cells derives from a non-permissive precursor population and depends on new mRNA synthesis. The current studies were designed to examine the effects of PRRSV on both infected and uninfected PAM cells in vitro, specifically focusing on the expression of MHC I, MHC II, CD14, CD163 and CD172a surface proteins. The results show upregulation of MHC II, CD14, CD163 and CD172a expression in PRRSV-infected cells and a downregulation on the uninfected cells within the PRRSV-inoculated cultures. The role of apoptosis in the PRRSV-inoculated cultures was investigated, with results showing similar, low levels of apoptosis in control and infected PAM. PAM cytokine responses to PRRSV and LPS were also examined and, although they were uniquely different relative to control PAM, no trends were detected in the responses of PAM infected with PRRSV compared to uninfected and classically stimulated PAM. These data confirm that there are at least two subsets of macrophages within the alveolar population and suggests that the subsets are differentially affected by PRRS virus. We also demonstrated that MHC I becomes undetectable on PAM as a result of the freezing process, and that PRRSV-permissiveness is greater in the cell population after freezing.
Keywords: PRRSV; Biology, Veterinary Science (0778)